Perancangan Aplikasi E-Voting Ketua OSIS Dan Wakil OSIS Pada SMK Nida El-Adabi Parung Panjang Berbasis Web - Usman; Arief Yulianto, Muhamad (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
This research aims to develop and test a web-based E-Voting application as an alternative solution for the election of the President and Vice President of the Student Council (OSIS) at SMK Nida El-Adabi Parung Panjang. Based on previous findings, the conventional election process took 6 hours until the winners were announced and faced challenges such as low student participation and the potential for vote counting errors. To address these issues, the E-Voting application was developed to facilitate online voting by students through their personal devices. The waterfall method was employed in the development of this application, encompassing stages such as requirements analysis, design, implementation, testing, and maintenance. This research aims to examine the effectiveness and accuracy of the E-Voting application in the election of the OSIS President and Vice President, as well as analyze its impact on student participation in the democratic process at school. The waterfall method has proven to be effective in the development of the E-Voting application, making it a valuable guide for other schools interested in adopting similar technology for their election processes. The research outcomes can provide a better understanding of the use of E-Voting in the context of OSIS elections and contribute to the development of democratic systems in the school environment.